Rezension von: Bever, Edward, The Realities of Witchcraft and Popular Magic in Early Modern Europe - Schmidt, Jürgen (Zeitschrift für Württembergische Landesgeschichte, 2013)
Edward Bever: The Realities of Witchcraft and Popular Magic in Early Modern Europe: Culture, Cognition, and Everyday Life (Palgrave Historical Studies in Witchcraft and Magic). Basingstoke: Palgrave Macmillan 2008. 648 S. ISBN 978-1-4039-9781-4. £ 65,–